2013
DOI: 10.1021/es4016266
|View full text |Cite
|
Sign up to set email alerts
|

Exposure Chambers for Studying the Partitioning of Atmospheric PAHs in Environmental Compartments: Validation and Calibration Using Experimental and Computational Approaches

Abstract: The environmental partitioning of atmospheric polycyclic aromatic hydrocarbons (PAHs) conditions their entry into food chains and subsequent risks for human health. The need for new experimental exposure devices for elucidating the mechanisms governing ecosystemic PAH transfer motivated the elaboration of an original small-scale exposure chamber (EC). A dual approach pairing experimentation and computational fluid dynamics (CFD) was selected to provide comprehensive validation of this EC as a tool to study the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…These CV% values are less than those obtained in earlier studies using other types of passive air samplers, e.g., activated carbon. 25 In addition, a significant correlation was established between the PUF plugs measurements and C air , acquired from concentrations in the PUF plugs at the outlet, which indicated that PUF plugs at the outlet could reliably reflect the HBCDs concentrations in the air phase (R 2 = 0.916, p = 0.000; Figure S2).…”
Section: ■ Results and Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…These CV% values are less than those obtained in earlier studies using other types of passive air samplers, e.g., activated carbon. 25 In addition, a significant correlation was established between the PUF plugs measurements and C air , acquired from concentrations in the PUF plugs at the outlet, which indicated that PUF plugs at the outlet could reliably reflect the HBCDs concentrations in the air phase (R 2 = 0.916, p = 0.000; Figure S2).…”
Section: ■ Results and Discussionmentioning
confidence: 85%
“…The coefficient of variation (CV%) values for the measured concentrations recovered from the PUF plugs at various sites within the ECs were less than 5.97% (Table S5), indicating there existed adequate atmospheric HBCDs mixing in the ECs and the reproducibility of the PUF plugs. These CV% values are less than those obtained in earlier studies using other types of passive air samplers, e.g., activated carbon . In addition, a significant correlation was established between the PUF plugs measurements and C air , acquired from concentrations in the PUF plugs at the outlet, which indicated that PUF plugs at the outlet could reliably reflect the HBCDs concentrations in the air phase ( R 2 = 0.916, p = 0.000; Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…In studying goals, the most suitable shrub for green urban spaces to efficiently moderate atmospheric pollution by PAHs can be selected. Given that the molecular weight of PAHs is related to their distribution among the gaseous phase and the particle-bond fraction of the atmosphere (low molecular weight PAHs are predominantly present in the gaseous phase while higher molecular weight PAHs are linked to the large particle fractions) (Desalme et al, 2013), the present study discriminates the pollutants according to the number of rings of which they are formed.…”
Section: Introductionmentioning
confidence: 99%